An acoustic microscope in measurements of mechanical properties of surface layers – V(z) - LITNIEWSKI, Jerzy (Archives of Acoustics, 1986)
The V(z) measuring technique, i.e. the application of the acoustic micro-scope as a measurement tool is presented and explained. In the measurements, the pressure amplitude distribution on the surface of the lens is controlled in a certain range, enabling V(z) curves to be optimized with respect to oscillation amplitudes obtained for the given material. V(z) curves obtained with this set-up and calculated from them Rayleigh wave velocities are included in the paper. The possibility of using such a set-up in thin film measurements has been pointed out.